Estudio de la aplicación de zinc en el desarrollo y producción de variedades mejoradas de fréjol (Phaseolus vulgaris L.) en la zona de La Portada, Provincia del Carchi - Madera Mena, Vinicio Antonio (2018)
VII. SUMMARY The study was carried out in the province of Carchi, Canton Mira, San Nicolás de Uyamá sector at a latitude of 00 ° 32 "05.1 and a western longitude of 078 ° 02" 14.3, at an altitude of 2111 meters above sea level. The factors studied were; factor A: varieties of beans (1; valley red, 2; Centennial, 3; Cargabello), factor B: application dose of zinc (1, without application, 2; average, 3, high), theoretical methods were used: Inductive-deductive, analysis-synthesis and the empirical so-called experimental. The tasks performed to comply with the investigation were; Soil preparation, fertilization, furrow elaboration, delimitation of plots, sowing, applications of zinc, pest control, irrigation, harvest, the following variables were evaluated; height of the plant, days to harvest, length of pod, number of pods / punch, weight of 100 grains, pod yield and treatments were analyzed economically. Where it was determined that the Centenario variety obtained significant averages in the evaluations of; precocity of the varieties in terms of days to harvest length of pods, weight of 100 grains and yield per experimental unit, the high dose reported higher plant height, number of pods, weight of 100 grains and yield per experimental unit, attributing that the crop requires high doses of zinc, to reach the optimum development of the crop. Treatment T3 (Centennial-High Dose) showed less precocity in terms of days to harvest, length of pod, weight of 100 grains and yield per experimental unit, greater economic profitability, showing that the combination of these two evaluated factors, is ideal to obtain quality production and development of bean crops in the study area.